Sex Education by Parents to Prevent Child Sexual Abuse: Scoping Review - Nisa, Ananda Fadila; Ismarwati, Ismarwati (Buletin Penelitian Kesehatan, 2025)
Background: Child sexual abuse (CSA) is a global health problem with significant health consequences. Parents have an important role in providing sex education to prevent CSA. The research aims to examine parent’s attitudes, barriers, practices in providing sex education to prevent their children from sexual abuse. Methods: A scoping review research design using database searches from Pubmed, Scopus, Ebsco, SpringerLink, ScienceDirect, and manual searches carried out in 2019-2023, with the search words “parent*” AND “sex education” AND “prevent” OR “intervention” AND “child sexual abuse”. This article follows the Joanna Briggs Institute (JBI) scoping review framework to evaluate the studies Results: Obtained were 1061 articles, and then filtering was carried out based on inclusion and exclusion criteria and assessment of eligibility to obtain 10 articles that met the requirements. Results show that most parents believe in the importance of sex education for self-protection, though many face barriers such as embarrassment and lack of accurate information. Positive attitudes and open practices are crucial in delivering effective sex education. Conclusion: Parents play a crucial role in sex education to prevent child sexual abuse. They create a safe environment, teach body awareness, and foster self-confidence.